Pembelajaran berasaskan projek dalam kalangan guru pelatih Institut Pendidikan Guru Malaysia : Satu kajian kes - Nasir, Hasan (2014)
This research aims to identify the professional skills of teaching practices resulting from the implementation of project-based learning (PBP) in the teacher training area of study in Design and Technology. This qualitative case study aims to explore the focus on thinking skills practice, collaborative learning practice and value practice in the learning situation.This study involved six participants who were selected from two classes via purposive sampling. Two lecturers who were involved during the learning process were also interviewed. Data was collected using the survey method, observation and interviews. Data collected in the form of audio and video recordings were transcripted and analyzed via content analysis. The study found that there are: (1) Seven elements of thinking skills i.e sorting by priority, creating sequence, comparing and differentiating, generating ideas, linking, and innovative and creative problem solving; (2) three elements of collaborative learning i.e. sharing of ideas, peer-learning, and sharing information amongst each other and (3) seven elements of values i.e. patience, competitiveness, efficiency, voluntariness, teamwork, proactive traits and social skills. The study also found that the elements of self-attitude, time constraint, equipment and material needs as well as the expenditure posed as the obstacles and challenges during the implementation of the PBP. All the elements identified have been applied by the teacher trainees during the Bachelor of Teaching programme in the IPGMs. Generally, the study shows that the implementation of the PBP in the learning process could bring great impact towards building a highly skilled, creative and innovative, and a highly productive human capital, who are also endowed with personal and ethical qualities. The implications of this study are expected to be beneficial to the education‟s field, lecturers who performed the PBP, as well as to the IPGM‟s management.